Annexin-V positive extracellular vesicles level is increased in severe COVID-19 disease - Jacob, Valentine; Lambour, Alexis; Swinyard, Benjamin; Zerbib, Yoann; Diouf, Momar; Soudet, Simon; Brochot, Etienne; Six, Isabelle; Maizel, Julien; Slama, Michel; Guillaume, Nicolas (Frontiers in Medicine, 2023)
Objectives To evaluate extracellular vesicles levels in a cohort of SARS-CoV-2’s patients hospitalized in an intensive care unit with and without COVID-19 associated thromboembolic events. Methods In this study, we aim to assess endothelial and platelet membrane-derived extracellular vesicles levels in a cohort of SARS-CoV-2 patients with and without COVID-19-associated thromboembolic events who were hospitalized in an intensive care unit. Annexin-V positive extracellular vesicles levels were prospectively assessed by flow cytometry in one hundred twenty-three critically ill adults diagnosed with acute respiratory distress syndrome associated with a SARS-CoV-2 infection, ten adults diagnosed for moderate SARS-CoV-2 infection and 25 healthy volunteers. Results On our critically ill patients, thirty-four patients (27.6%) had a thromboembolic event, Fifty-three (43%) died. Endothelial and platelet membrane-derived extracellular vesicles were drastically increased in SARS-CoV-2 patients hospitalized in the ICU compared to healthy volunteers. Moreover a slighty higher small/large ratio for platelets membrane-derived extracellular vesicles in patients was linked to thrombo-embolic events. Conclusion A comparison between total annexin-V positive extracellular vesicles levels in severe and moderate SARS-CoV-2 infection and healthy controls showed a significant increase in patients with severe infection and their sizes could be considered as biomarkers of SARS-CoV-2 associated thrombo-embolic events.